O que vive em nós - Souza (Guarani), Emerson; Rosalen, Juliana; Gonçalves, Lucila de Jesus Mello; Moreira, Priscila Ambrósio; Barbalho, Thiago; Kehl, Maria Rita Bicalho (Percurso, 2021)
Realização: Camila Junqueira, Cristiane Abud Curi, Gisela Haddad, Ivy Semiguem, Thiago Majolo e Vera Zimmermann